Terapia oclusal con placas - Gerardo Becerra-Santos; Alejandro Peñaloza-H; Isabel C. Cataño; Olga Gomez; Ivan D Roman; Juan F. Escobar; Sisney Valencia; Pablo A Londoño (Universidad de Antioquia, 1995)
Occlusal plates constitute alternative solutions to muscular and articular problems. When there are etiological factors in the muscular and articular disorders, occlusal plate is recornended to have a reversible and not invasive initial therapy. Then, it is extremely important to identify the cause-effect relationship before the irreversible theraphy starts.